Characterization of the complete plastome of Ophrys aveyronensis, a Euro-Mediterranean orchid with an intriguing disjunct geographic distribution - Joris A. M. Bertrand; Anaïs Gibert; Christel Llauro; Olivier Panaud (Mitochondrial DNA. Part B. Resources, 2019)
Ophrys aveyronensis is an orchid with disjunct geographic distribution. For biogeographic and conservation purpose, we sequenced its complete plastome using Illumina data. The complete plastome is 146,816 bp in length, consisting of a pair of inverted repeats (IRs) of 25,006 bp, a large single-copy (LSC) region and a small single-copy region (SSC) of 80,495 and 16,309 bp, respectively. It was found to contain 133 genes, including 86 protein-coding genes, up to 39 trRNA genes and 8 rRNA genes. The overall GC content of the plastid genome is 36.9%. Phylogenetic inference confirms that O. aveyronensis is very close to O. sphegodes.